2013
DOI: 10.3389/fcimb.2013.00047
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of tsetse natural infection rates in the Mouhoun river, Burkina Faso, in relation with environmental factors

Abstract: In Burkina Faso, the cyclical vectors of African animal trypanosomoses (AAT) are riverine tsetse species, namely Glossina palpalis gambiensis Vanderplank (G.p.g.) and Glossina tachinoides Westwood (G.t.) (Diptera: Glossinidae). Experimental work demonstrated that environmental stress can increase the sensitivity of tsetse to trypanosome infection. Seasonal variations of the tsetse infection rates were monitored monthly over 17 months (May 2006–September 2007) in two sites (Douroula and Kadomba). In total, 1423… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…The present findings also showed that trypanosome prevalence is different between male and female flies. These results are similar to those found elsewhere [9,28]. The infection was due to three species and subspecies: T. congolense savannah predominated, followed by T. brucei brucei and T. brucei gambiense.…”
Section: Discussionsupporting
confidence: 91%
“…The present findings also showed that trypanosome prevalence is different between male and female flies. These results are similar to those found elsewhere [9,28]. The infection was due to three species and subspecies: T. congolense savannah predominated, followed by T. brucei brucei and T. brucei gambiense.…”
Section: Discussionsupporting
confidence: 91%
“…Temporal abundance of tsetse flies was estimated by monthly sampling for a period of 15 months in 2014 and 2015 in the village of Emboreet, which borders Tarangire National Park (Figure ). Sites were selected through stratified random subsampling of the major vegetation types in the area (Bouyer et al ). A total of ten sites were identified and three epsilon traps were deployed at each site and located at least 200 m apart (Malele et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Increasing the number of livestock in farmlands drastically alters the subSaharan African environment by modifying not only the livestock distribution, but also the distribution of tsetse flies that feed on it (and possibly their nutritional behavior). Indeed, the importance of environmental factors to transmission intensity and trypanosome distribution is increasingly being recognized (Van den Bossche et al, 2010;Bouyer et al, 2013). Accordingly, a recent study of climate change effects on the evolution of African trypanosomiasis predicts that 46-77 million additional people will be at risk of sleeping sickness by 2090 (Moore et al, 2012).…”
Section: Global Changes and Sleeping Sickness Transmissionmentioning
confidence: 99%